Aunty and Her Little Villains: The BBC and the Unions, 1969-1984 - Anthony McNicholas (tripleC: Communication, Capitalism & Critique)
This article charts industrial relations in BBC television from 1969-84. It is based upon extensive archival research of material not previously available, and witness seminars and interviews with some of the protagonists. This was a period which saw a rise in industrial militancy at the BBC, signalled by the first ‘lightning’ strikes in the BBC’s history in 1969 and ending with a strike in the scenic services department in 1984, in the course of which BBC TV went off the air for twenty four hours but BBC management reasserted its control. In the intervening period, some groups of workers were able to secure advantageous terms and conditions for themselves, to the frustration of both management and the main BBC union, the Association of Broadcasting Staff (ABS). This article offers a detailed and nuanced analysis of industrial relations at an important British cultural institution in a turbulent period of its history.